PENGARUH PEMBERIAN EKSTRAK AIR SAMBILOTO (Andrographis paniculata) TERHADAP PERTUMBUHAN DAN PROFIL LIPID AYAM PETELUR FASE STARTER: Effect of Andrographis (Andrographis paniculata) Aqueous Extract Administration on Growth Performance and Lipid Profile of Starter-Phase Laying Hens - Darmansyah; A Mujnisa; Wempie Pekiding; Ummi Amanah; Riska Amelia; Triami Lestari; Fachrul Akbar (Faculty of Animal Science, University of Tulang Bawang, 2026)
The starter phase (0–6 weeks) is a critical period for laying hens that determines future production potential, characterized by the intensive development of the digestive system and vital organs. The global prohibition of Antibiotic Growth Promoters (AGP) necessitates the exploration of natural alternatives such as Sambiloto (Andrographis paniculata) phytobiotics. This study aims to empirically test the effect of Sambiloto Leaf Extract (SLE) dosage administered via drinking water on the growth performance and blood cholesterol profile. The research utilized a Completely Randomized Design (CRD) with five treatments: T1 (0% SLE), T2 (0.5%), T3 (1.0%), T4 (1.5%), and T5 (2.0% SLE). A total of 100 Isa Brown strain chicks were monitored over six weeks. Parameters observed included the blood cholesterol profile, drinking water intake (DWI), feed intake (FI), body weight gain (BWG) and feed conversion ratio (FCR). Results indicated that SLE administration significantly (P<0.05) reduced serum total cholesterol (up to 22.97%) and triglyceride levels (up to 28.36%) in high-dose groups (T3, T4, T5). This hypolipidemic effect is attributed to andrographolide inhibiting key enzymes in cholesterol synthesis. Conversely, SLE did not significantly affect (P>0.05) HDL or LDL levels, nor did it significantly impact growth performance parameters. However, the 2.0% dose (T5) demonstrated the most optimal positive trend, recording the highest BWG (11.24 g/bird/day) and the lowest FCR (2.57). It is concluded that SLE is well-tolerated and serves as an effective phytogenic feed additive to improve lipid profiles without compromising palatability or performance. Keywords: blood cholesterol, laying hens, phytobiotics, sambiloto, starter phase